Profil Hematologi Penderita Demam Tifoid Yang Dirawat Inap Di RSUD Labuang Baji Makassar Tahun 2021-2022 - Lukman, Nur Annisa; Syamsuddin, Fatmawati Annisa; Hariadi, Anisyah (Bosowa Medical Journal, 2024)
Typhoid fever is an acute systemic infectious disease that attacks the reticuloendothelial system, gastrointestinal lymph nodes, and gallbladderMost typhoid fever patients experience hematological changes such as anemia, leukopenia, eosinophilia, thrombocytopenia, and subclinical disseminated intravascular coagulation. Most also had a slight increase in prothrombin time (PT) and partial activated thromboplastin time (APTT) and decreased levels of circulating fibrinogen and fibrin degradation products. The research objective was to find out how the distribution of typhoid fever sufferers was based on (1) age, (2) gender, (3) leukocytes, (4) neutrophils, (5) lymphocytes (6) platelets and (7) hemoglobin. This study included 118 typhoid fever patients who were admitted to the Labuang Baji Hospital Makassar in 2021-2022. This study used a descriptive method and a retrospective study design, using secondary data in the form of medical records of patients with typhoid fever who were hospitalized at Labuang Baji Hospital Makassar. Data analysis was processed using SPSS software. The results of this study show the distribution of typhoid fever sufferers who are hospitalized at Labuang Baji Makassar Hospital in 2021-2022, that is: (1) The most common age of typhoid fever sufferers is 17-25 years old (42.4%), (2) More are women ( 63.6%) than men (36.4%), (3) More normal leukocytes (83.9%) than leukopenia (17.8%) and leukocytosis (16.1%), (4) More normal neutrophils (71.2%) than neutropenia (14.4%) and neutrophilia (14.4%) with the same proportion, (5) More number of normal lymphocytes (67.8%) than lymphocytopenia (29.7%) and lymphocytosis (2.5%), (6) More number of normal platelets (61.9%) compared to thrombocytopenia (37.3%) and thrombocytosis (0.8%), (7) More hemoglobin with anemia (58.5%) than normal (41.5%). The study concluded that most patients with typhoid fever hospitalized at Labuang Baji Hospital in Makassar in 2021-2022 were aged 17-25 years and experienced mainly by women with normal leukocyte, neutrophil, lymphocyte, and platelet counts and anemia hemoglobin.